The Impact of Artificial Intelligence (AI) in Stoichiometry Learning on Problem-Solving Skills of Senior High School Students in Phase F - Sabila Zeolita; Rayandra Asyhar; Asrial Asrial; Muhammad Naswir; Yusnidar Yusnidar; Asmiyunda Asmiyunda (Pusat Publikasi Ilmiah, STKIP Taman Siswa Bima, 2026)
This research was motivated by students’ low problem-solving skills in stoichiometry and the increasing integration of Artificial Intelligence (AI) in learning. Chemistry learning, particularly stoichiometry, still presents difficulties in understanding concepts and determining systematic problem-solving steps. Therefore, this study aimed to analyze the effect of AI use in stoichiometry learning on the problem-solving skills of high school students in phase F. This study employed a quantitative method with a true experimental design using a pretest-posttest control group design. The sample consisted of an experimental group (XI-F4), which received AI, and a control group (XI-F5), which learned without AI. Data were collected through essay tests (pretest and posttest) and a student response questionnaire. The instruments were tested beforehand to ensure validity and reliability. Data analysis included normality, homogeneity, Independent Sample t-test, and N-Gain tests using SPSS Statistics version 29 and Microsoft Excel 2025. The results showed no significant effect of AI on students’ problem-solving skills (0.152 > 0.05), although N-Gain and student responses indicated AI’s potential as a learning support tool.